1978
DOI: 10.1037/0003-066x.33.10.920
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating psychological research reports: Dimensions, reliability, and correlates of quality judgments.

Abstract: A series of studies designed to investigate three major aspects of the peer-evaluation system in psychology is presented. Editors and editorial consultants for nine major psychology journals were surveyed for opinions about the desirability of article characteristics. Dimensional structures for evaluation were explored, resulting in a set of prescriptive norms for assessment. Substantial agreement on the desirability of article characteristics is demonstrated, and psychologists heavily involved in the manuscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(110 citation statements)
references
References 43 publications
2
104
0
4
Order By: Relevance
“…This put it in the top 25% of general biological science journals and nearly as high as Psychological Science (4.7). This casts further doubt on reviewers' ability to predict importance (Gottfredson, 1978) or at least one indicator of importance: citation impact. With a publishing model focused on soundness, negative results and replications are more publishable, and the journal identity is not defined as publishing research that is otherwise unpublishable.…”
Section: Journals With Peer Review Standards Focused On the Soundnessmentioning
confidence: 99%
See 1 more Smart Citation
“…This put it in the top 25% of general biological science journals and nearly as high as Psychological Science (4.7). This casts further doubt on reviewers' ability to predict importance (Gottfredson, 1978) or at least one indicator of importance: citation impact. With a publishing model focused on soundness, negative results and replications are more publishable, and the journal identity is not defined as publishing research that is otherwise unpublishable.…”
Section: Journals With Peer Review Standards Focused On the Soundnessmentioning
confidence: 99%
“…Many manuscripts are rejected on this criterion, even if the reviewers identify the research as sound and reported effectively. Despite evidence of the unreliability of the review process for evaluation and identifying importance (Bornmann, Mutz, & Daniel, 2010;Cicchetti, 1991;Gottfredson, 1978;Marsh & Ball, 1989;Marsh, Jayasinghe, & Bond, 2008;Peters & Ceci, 1982;Petty, Fleming, & Fabrigar, 1999;Whitehurst, 1984), this is a reasonable criterion given that journals have limited space and desires to be prestigious outlets. However, in the digital age, page limits are an anachronism (Nosek & Bar-Anan, 2012).…”
Section: Journals With Peer Review Standards Focused On the Soundnessmentioning
confidence: 99%
“…However, editors and referees may agree about properties that constitute true value but be unable to perceive true value accurately. Gottfredson (1978), Gottfredson and Gottfredson (1982), and Wolff (1970) found that reviewers for psychological journals agree rather strongly about properties that manuscripts ought to possess, but their judgments about whether specific manuscripts possess various properties agree much less strongly; correlations ranged from 0.16 to 0.50.…”
Section: What Is the Value Of A Manuscript?mentioning
confidence: 99%
“…There is no way to directly measure reviewers' abilities to discern manuscripts' true values, but two kinds of observations offer tangential evidence about these abilities. First, Gottfredson (1977Gottfredson ( , 1978 found that reviewers' forecasts of manuscripts' impacts correlated only 0.37 with later citations and their ratings of manuscript quality correlated only 0.24 with later citations. If true values are less visible and more difficult to discern than citation values, correlations of reviewers' judgments with manuscripts' true values are lower than these correlations.…”
Section: What Is the Value Of A Manuscript?mentioning
confidence: 99%
See 1 more Smart Citation